PENINGKATAN HASIL BELAJAR MAPEL IPS MENGGUNAKAN METODE DISKUSI KELOMPOK SISWA KELAS V SDN 1 KARANGANYAR PATIKRAJA BANYUMAS - Sri Endah Wahyuni (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
The purpose of this research is to increase learning outcomes/result of 5th grade SDN 1 Karanganyar Patikraja Banyumas for Social lesson with the topic to Appreciating the Characters Struggle to maintain independence through the application of the group discussion method. This Research is using Classroom Actions Research which implemented in two cycles, each cycle consisting of four stage, those stages are planning/designs, actions, observations, and reflections. Data collection can be done by test, observation and questionnaire. Indicator of the success of actions in this research is if the increasing of learning outcomes is at least 85% from all students has reach KKM of Social lesson 68. This research conclude that: Application of the group discussion method can increase outcomes/result learning in social lesson for the topic to Appreciating the Characters Struggle to maintain independence of 5th grade SDN 1 Karanganyar Patikraja Banyumas in academic year 2013 – 2014. it is seen from the student learning outcomes score in the cognitive cycle 1 to obtain an average of 74 to 88% of completeness, in cycle 2 increased to an average score of 82 to 100% completeness. The psychomotor domain of learning outcomes scores obtained in cycle 1 at 79 with good categories, and has increase in cycle 2 to 83 with good category too. The affective domain of learning outcomes in cycle 1 scores obtained at 81 and increased to 83 in cycle 2 with both excellent categories. Keywords : Learning Motivations, Learning Outcomes, Scientific Approach, Group Discuss Method